1993
DOI: 10.1210/jcem.77.4.8408448
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-modulated stromal cell tissue factor expression: a model for the regulation of endometrial hemostasis and menstruation.

Abstract: This study examined steroidal regulation of tissue factor expression by cultured endometrial stromal cells. Confluent stromal cell cultures derived from cycling human endometria were exposed to vehicle control, 10(-8) mol/L estradiol (E2), 10(-8)-10(-6) mol/L medroxyprogesterone acetate (MPA), or both E2 and MPA for 2-24 days in serum-containing medium. The progestin enhanced immunoreactive and functionally active stromal cell tissue factor content, achieving peak effects by 8-12 days of culture. Although E2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 15 publications
5
43
0
Order By: Relevance
“…TF is the primary initiator of haemostasis generating fibrin and leading to clot formation ( Fig. 1; Lockwood et al 1993). Fibrinolysis leading to clot degradation is regulated by the availability of plasmin by the action of PA. Progesterone increases TF expression but decreases PA expression, therefore progesterone withdrawal immediately prior to menstruation induces a haemorrhagic environment with decreased clotting and increased fibrinolysis (Casslen et al 1995).…”
Section: Menstruationmentioning
confidence: 99%
“…TF is the primary initiator of haemostasis generating fibrin and leading to clot formation ( Fig. 1; Lockwood et al 1993). Fibrinolysis leading to clot degradation is regulated by the availability of plasmin by the action of PA. Progesterone increases TF expression but decreases PA expression, therefore progesterone withdrawal immediately prior to menstruation induces a haemorrhagic environment with decreased clotting and increased fibrinolysis (Casslen et al 1995).…”
Section: Menstruationmentioning
confidence: 99%
“…30,39 -41 We have also shown that glandular epithelial cells display minimal TF expression throughout the menstrual cycle. 30,39,40 The present study sought to determine the pattern and extent of TF expression in endometriosis and observed anomalous endothelial expression of TF in ectopic versus eutopic endometrium. This expression likely reflects the strong association of endometriosis with increased inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…TF is a 262-amino acid membrane-bound glycopeptide whose expression in ES cells, in vivo and in vitro, mimics that of decidual PRL (13,16,17). Serum factors are known to induce TF expression in several cell types, including ES cells, and consequently confluent cultures were maintained in low serum (2% DCC-FBS) for 48 h before treatment with cAMP, IFN␥, or their combination.…”
Section: Ifn␥ Induces Tissue Factor (Tf) Expression In Es Cellsmentioning
confidence: 99%
“…In human endometrium, TF expression has been reported to be closely associated with decidual transformation and is often used as a biochemical marker of this differentiation process (13,16,17). The distinct temporal and spatial expression of TF in the endometrium indicates a pivotal role in maintaining vascular integrity before menstruation and, if pregnancy occurs, during intravascular trophoblast invasion (16,17). We previously reported that TF expression in primary cultures mimics that of PRL, characterized by rapid induction in response to cAMP treatment, which is further enhanced by the addition of progestins.…”
Section: Ifn␥ Modulates Decidualizationmentioning
confidence: 99%
See 1 more Smart Citation